Kemasan Antimikrob untuk Memperpanjang Umur Simpan Bakso Ikan - Endang Warsiki; Titi Candra Sunarti; Lala Nurmala (Jurnal Ilmu Pertanian Indonesia, 2013)
Active packaging is a technique that can be developed to prolong shelf-life or enhance safety or sensory properties, while maintaining the quality of fresh products inside. This experiment produced active packaging of antimicrobial (AM) film in which an antimicrobial (AM) agent was added into the film (instead of food) and then used it to coat the food product. The AM agents slowly release into the product surrounds, inhibit the growth of microbes thus packing and preserving were done in a single step. Carragenan was chosen as a matrix film with garlic extract as an AM agent. Fish balls were chosen as a product to be coated by this AM film. The study consisted of 2 steps i.e.: (i) prepared AM film, and (ii) coated the fish balls with AM film and then tested the quality during storage. In general, the quality of fish balls before and after storage still meet the SNI 0-3819-1995. In the application, the fish balls with AM film has longer shelf life than that without AM. Further more, the result of organoleptic test on appearance of odor and color showed that the panelists prefered coated fish balls than the uncoated one. The panelist prefered coated fish ball which is stored at 5 and 15°C.